The prevalence of emotional eating and its relation to affect regulation in a Turkish sample of obese, overweight and normal weighted women - Evirgen, Nur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2010., 2010)
This study investigated the prevalence of emotional eating and binge eating and their relation to variables associated with affect regulation within different weight categories. Emotional eating and binge eating have been associated to unhealthy eating patterns leading to health problems such as obesity, which is defined to be a biological, psychological and social epidemic. Participants in this study were comprised of 204 women with body mass index ranging from 16.9 to 52.07, ninetyeight of which were receiving professional intervention for weight loss. The Dutch Eating Behavior Questionnaire and Bulimia Investigatory Test Edinburg were used to assess eating styles and binge eating. Negative Mood Regulation Expectancies Scale, Trait Anger and Anger Expression Scales and the Toronto Alexithymia Scale were used to assess psychological variables related to affect regulation. The prevalence of emotional eating was found to be significantly higher in obese and overweight samples compared to the normal weighted sample. Results implied binge eating to be a form of emotional eating. Furthermore emotional eating and binge eating were found to be associated to variables related to affect regulation. Implications of the results in the light of previous studies, and recommendations for future research are discussed.
Keywords: Compulsive eating.; Eating disorders.; Food habits -- Psychological aspects.; Weight loss -- Psychological aspects.; Nutrition -- Psychological aspects.